PENERAPAN DISCOVERY LEARNING BERBANTUAN VIRTUAL LABORATORY UNTUK MENINGKATKAN KOMPETENSI FISIKA SISWA SMA - Masril Masril; Hidayati Hidayati; Yenni Darvina (Postgraduate, University of Mataram, 2019)
The purpose of this study is to determine the effect of implementation virtual labs through discovery learning in senior high school. The population of the study was students of SMAN 12 Padang and the sample was two classes with cluster random sampling technique. Students were divided into two groups: experimental and control group. The research instrument used for competency of attitude is observation sheet, for competence of knowledge is multiple choice and for skill competence using working assessment. Based on the results of the research, it can be concluded that for the three competencies shows the results that the experimental class is better than the control class.